Is work in Europe decent? A study based on the 4th European survey of working conditions 2005 - Andranik Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2007)
Composite indicators of Decent work for 31 European countries are constructed with the data of the Fourth European Working Conditions Survey 2005 (EWCS 2005). Partial indices reflect 15 aspects of working conditions as in the recently published German DGBindex Gute-Arbeit. In a sense, the German indicator is extended to European data. Two methodologies, of the OECD and of the Hans Böckler Foundation, differing in scaling, give very similar results. The main findings are as follows: 1. Evaluation of working conditions. Working conditions are evaluated on the average with 61 conditional % (= low medium level), ranging from 51 in Turkey (inferior level) to 67 in Switzerland (upper medium level). A good evaluation (> 80) is inherent only in the meaningfulness of work (81). Two aspects got a bad evaluation (< 50): qualification and development possibilities (33) and career chances (49). 2. Importance of different aspects of working conditions. Stepwise regression reveals that job stability is the most important factor for the satisfaction with working conditions. Strains, career chances, meaningfulness of work go next. Income and collegiality are ranked 5th or 6th, depending on the evaluation method. Creativity and industrial culture make no statistically significant impact. Learning and good management are regarded as shortcomings rather than as advantages. 3. Disparities among countries and social groups. The evaluation shows significant disparities among European countries and social groups. Those who work in finances have by far better working conditions, even comparing with the next best group of business people, women have worse working conditions than men with respect to 9 of 15 aspects, and all types of atypical employees (other than permanent employees) have working conditions below the European average, to say nothing of those with permanent contract. 4. Role of strong trade unions for job stability. A high job stability is observed in some countries with relaxed employment protection and strong trade unions. At the same time, a low job stability is inherent in some countries with strict employment protection but weak trade unions. It means that the institutional employment protection alone does not guarantee job stability, and other factors, like strong trade unions, can be even more important. To stimulate employers to equalize working conditions it is proposed to introduce a workplace tax for bad working conditions which should protect 'the working environment' in the same way as the green tax protects the natural environment. Indexing working conditions at every workplace developed in our study can be regarded as prototype measuring the 'social pollution' and used to determine the tax amount.
Keywords: C43; C51; J21; J88; 330; Composite indicators; quality of work; European Union; statistical indices; processing qualitative and ordinal data; Arbeitsbedingungen; Qualitatives Verfahren; Schätzung; Europa